Cardiomyopathy due to PRDM16 mutation: First description of a fetal presentation, with possible modifier genes. Issue 1 (22nd January 2020) - Delplancq, Geoffroy; Tarris, Georges; Vitobello, Antonio; Nambot, Sophie; Sorlin, Arthur; Philippe, Christophe; Carmignac, Virginie; Duffourd, Yannis; Denis, Charlotte; Eicher, Jean Christophe; Chevarin, Martin; Millat, Gilles; et al.
Abstract: PRDM16 (positive regulatory domain 16) is localized in the critical region for cardiomyopathy in patients with deletions of chromosome 1p36, as defined by Gajecka et al., American Journal of Medical Genetics, 2010, 152A, 3074–3083, and encodes a zinc finger transcription factor. We present the first fetal case of left ventricular non‐compaction (LVNC) with a PRDM16 variant. The third‐trimester obstetric ultrasound revealed a hydropic fetus with hydramnios and expanded hypokinetic heart. After termination of pregnancy, foetopathology showed a eutrophic fetus with isolated cardiomegaly. Endocardial fibroelastosis was associated with non‐compaction of the myocardium of the left ventricle. Exome sequencing (ES) identified a de novo unreported p.(Gln353*) heterozygous nonsense variant in PRDM16 . ES also identified two rare variants of unknown significance, according to the American College of Medical Genetics and Genomics guidelines, in the titin gene ( TTN ): a de novo missense p.(Lys14773Asn) variant and a c.33043+5A>G variant inherited from the mother. Along with the PRDM16 de novo probably pathogenic variant, TTN VOUS variants could possibly contribute to the severity and early onset of the cardiac phenotype. Because of the genetic heterogeneity of cardiomyopathies, large panels or even ES could be considered as the main approaches for the molecular diagnosis, particularly in fetal presentations, where multiple hits seem to be common.